THE ANALYSIS OF ROBINSON CRUSOE’S AMBITION IN DANIEL DEFOE’S ROBINSON CRUSOE NOVEL: Robinson Crusoe, Ambition - Niswatin Hasanah; Ika Trisnantasari; Risma Kartika Dewi (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2023)
This study discusses the meaning of life, travel and advocacy about the main character. The researcher was interested in analyzing the ambition of main character in the novel Robinson Crusoe from Daniel Defoe because the main character in the novel Robinson Crusoe interpreted a man in real life. Researchers who have succeeded in finding meaning behind characters are always a mystery. A person's ambition can be influenced by several factors. To know ambition, humans are required to know themselves. Many writers try to express their ideas about life, one of which is Daniel Defoe in his novel titled Robinson Crusoe. He described the discovery of the meaning of one's life through the journey of the main character named Crusoe from one island to another. This thesis focuses on the ambitions of Robinson Crusoe in traveling, Crusoe who guides himself to find the meaning of his life. Crusoe really wants to sail with the purpose of his life can change but Crusoe does not know what happened on the trip, the purpose of this thesis is to describe the character of Crusoe and the background that caused him to travel and describe the experiences experienced by Crusoe in his journey so he managed to formulate the value of life that led him to find his identity and meaning in life as a human being.